Trends in Endovascular Therapy and Clinical Outcomes Within the Nationwide Get With The Guidelines-Stroke Registry. Issue 4 (April 2015) - Menon, Bijoy K.; Saver, Jeffrey L.; Goyal, Mayank; Nogueira, Raul; Prabhakaran, Shyam; Liang, Li; Xian, Ying; Hernandez, Adrian F.; Fonarow, Gregg C.; Schwamm, Lee; Smith, Eric E.
<x xml:space="preserve">Abstract</x> Background and Purpose— We sought to determine hospital and patient characteristics associated with the use of endovascular therapy for acute ischemic stroke and to analyze trends in clinical outcome. Methods— Data were from Get With The Guidelines-Stroke hospitals from April 1, 2003, to June 30, 2013. We looked at trends in number of hospitals providing endovascular therapy, the use of endovascular therapy in these hospitals and clinical outcomes. We analyzed hospital and patient characteristics associated with endovascular therapy use. Results— Of 1087 hospitals, 454 provided endovascular therapy to ≥1 patient in the study period. From 2003 to 2012, proportion of hospitals providing endovascular therapy increased by 1.6% per year (from 12.9% to 28.9%; P<0.0001), with a modest drop to 23.4% in 2013. Utilization of endovascular therapy increased from 0.7% to 2% (P<0.001) with a modest drop to 1.9% in 2013. The overall rate of symptomatic intracerebral hemorrhage among endovascular therapy treated patients was 9.7%. In multivariable analyses, patient outcomes after endovascular therapy improved over time, with reductions in in-hospital mortality (29.6% in 2004 to 16.2% in 2013; P=0.002); and from late 2010, reduction in symptomatic intracerebral hemorrhage (11% in 2010 to 5% in 2013; P<0.0001), increased independent ambulation at discharge (24.5% in 2010 to 33% in 2013; P<0.0001) and discharge home (17.7% in 2010 to 26.1% in 2013; P<0.0001). Trends for these outcomes persist in the analyses adjusted for baseline National Institutes of Health Stroke Scale. Conclusion— The use of endovascular therapy increased modestly nationally from 2003 to 2012 and decreased in 2013. Clinical outcomes improved notably from 2010 to 2013, coincident with more experience and newer thrombectomy devices.